Transvaginal Laparoscopic Appendectomy Simultaneously with Vaginal Hysterectomy: Initial Experience of 10 Cases - Tian, Yu (International Scientific Literature, Inc., 2014)
BACKGROUND: Natural orifice transluminal endoscopic surgery (NOTES) involves the introduction of instruments through a natural orifice into the peritoneal cavity to perform surgical interventions. The vagina is the most widely used approach to NOTES. We report the utilization of the vaginal opening at the time of vaginal hysterectomy as a natural orifice for laparoscopic appendectomy. MATERIAL/METHODS: We reviewed cases of 10 patients with chronic appendicitis who underwent transvaginal laparoscopic appendectomy simultaneously with vaginal hysterectomy. A laparoscopic approach was established after removal of the uterus, and the appendix was removed transvaginally. Among the 10 cases, 5 were conducted under gasless laparoscopy by using a simple abdominal wall-lifting instrument. RESULTS: All procedures were performed successfully without intraoperative or major postoperative complications. The appendectomy portion of the procedure took approximately 21 minutes to 34 minutes. All patients were discharged less than 4 days after surgery, without external scars. CONCLUSIONS: Transvaginal appendectomy with rigid laparoscopic instruments following vaginal hysterectomy appears to be a feasible and safe modification of established techniques, with acceptable outcomes.